Role of Surgical Biopsy in Thoracic Swellings - Ishtyak Ahmed Mir (International Journal of Medical Research and Review, 2015)
Background: Open Surgical biopsy as the first line of investigation is neither practiced by the clinicians nor liked by the patient. Non invasive diagnostic techniques are used for initial evaluation of a swelling, but these facilities are not available every where. The study was conducted to know the results of open surgical biopsy in patients with cervico thoracic and other body swellings.Material and Methods: The study included 49 patients, mostly females, majority in 2nd to 3rd decade of life, youngest a 7 year old girl and the eldest a 68 year old male. 75% of the patients presented with swelling, 100% had clinically palpable swelling and cervico thoracic region was involved in more than 90% of the patients. Under local anesthesia open surgical biopsy was done in all.Results: Histopathology revealed tuberculosis in 63.26% and malignancy in 20.40% of the patients. All patients with anterior chest wall swellings had malignancy. 79.59% of the patients were definitely helped by accurate diagnosis and specific treatment. There was no morbidity related to the surgical procedure.Conclusion: It is recommended that open surgical biopsy should always be performed in any patient with a suspicious swelling, and where facilities for non invasive investigation and sophisticated investigation are not available. It not only helps in making and excluding a diagnosis, but also helps in providing specific treatment to the patient.